The Effectiveness of Chunking Technique on the Mathematical Problem-Solving Skills of College Students - Ibañez, Edwin; Castro, Brix Lander; Collantes, Leila; Taganap, Eduard (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of the chunking technique in improving the mathematical problem-solving skills of college students. Chunking, a cognitive strategy grounded in Information Processing Theory, involves breaking information into meaningful units to reduce cognitive load and support working memory. Although widely discussed in psychology, its application in mathematics instruction—especially in teacher education—remains limited. To address this gap, a quasi-experimental pre-test–post-test design was employed among 60 college students enrolled in a state university during Academic Year 2025–2026. Participants were divided into a control group that received traditional instruction and a treatment group that received chunking-based lessons developed and validated by mathematics educators.Pre-test results indicated comparable baseline performance between groups. Post-test data, however, revealed considerably higher scores for the treatment group (M=33.20) compared to the control group (M=25.90), indicating significant improvement in mathematical problem-solving performance. Both groups also demonstrated significant gains from pre-test to post-test, though the treatment group’s improvement was notably greater. Qualitative feedback further reflected positive changes in students’ mathematical attitudes, particularly in confidence, strategy use, and perceived manageability of complex problems.Findings suggest that chunking can serve as an effective instructional strategy for teaching multi-step mathematical tasks in higher education. Beyond improving student performance, the approach offers a practical framework that may benefit future mathematics teachers, bridging the gap between cognitive research and classroom instruction.
Keywords: Mathematics Education, Learning Strategy, Chunking, College Mathematics